Development of a novel evaluation method by mathematical anatomy for foot bone alignment displacement using x-ray radiographs. - Yosuke Maruyama; Katsutoshi Itsukaichi; Naoya Hoshikawa; Takayuki Nakagomi; Tomohiro Matsuyama; Hiroyuki Sasaki (PLoS ONE)
The major methods of evaluating the foot arch in clinical practice in patients with foot deformities are medial longitudinal arch measurement using body surface somatometry and radiographic morphometry. Although these methods are widely used, they are considered problematic in terms of differences in scores between the methods. In this study, we developed a new geometric shape analysis method for the bony arrangement of the foot using the two-dimensional fast Fourier transform (2D-FFT), which incorporates mathematical anatomy using x-ray radiographs. Lateral radiographs of the foot bones were obtained using ImageJ2 provided by the National Institutes of Health. The 2D-FFT images show the characteristic directional power spectrum extending from low to high frequencies in the first and third quadrants on the normal, low and high arched foot respectively. The current method of reflecting the bone arrangement status of the metatarsal and tarsal bones may have the potential to establish a new radiographic evaluation method for assessing abnormal foot-bone alignment. As a result, the foot bone 2D-FFT method can be useful in assessing the medial longitudinal arch and predicting the prognosis of these patients.